ОБ'ЄКТ НЕНАЛЕЖНОГО ВИКОНАННЯ ОБОВЯЗКІВ ЩОДО ОХОРОНИ ЖИТТЯ ТА ЗДОРОВ'Я ДІТЕЙ - Бандурка, Ірина Олександрівна (SUPREMANCE OF LAW, 2016)
Article considers of socially dangerous act as improper performance of duties to protect life and health of children. The considered of theoretical approaches to the definition of the object of the crime. Highlight a common, genitive and direct objects of improper performance of duties to protect life and health of children.
Keywords: child; criminal legal protection; life; health; crime; the object of the crime